Alterations in White Matter Microstructure and Connectivity in Young Adults with Alcohol Use Disorder. (6th May 2019) - Chumin, Evgeny J.; Grecco, Gregory G.; Dzemidzic, Mario; Cheng, Hu; Finn, Peter; Sporns, Olaf; Newman, Sharlene D.; Yoder, Karmen K.
Abstract : Background: Magnetic resonance imaging (MRI) studies have shown differences in volume and structure in the brains of individuals with alcohol use disorder (AUD). Most research has focused on neuropathological effects of alcohol that appear after years of chronic alcohol misuse. However, few studies have investigated white matter (WM) microstructure and diffusion MRI–based (DWI) connectivity during early stages of AUD. Therefore, the goal of this work was to investigate WM integrity and structural connectivity in emerging adulthood AUD subjects using both conventional DWI metrics and a novel connectomics approach. Methods: Twenty‐two AUD and 18 controls (CON) underwent anatomic and diffusion MRI. Outcome measures were scalar diffusion metrics and structural network connectomes. Tract‐Based Spatial Statistics was used to investigate group differences in diffusion measures. Structural connectomes were used as input into a community structure procedure to obtain a coclassification index matrix (an indicator of community association strength) for each subject. Differences in coclassification and structural connectivity (indexed by streamline density) were assessed via the Network Based Statistics Toolbox. Results: AUD had higher fractional anisotropy (FA) values throughout the major WM tracts, but also had lower FA values in WM tracts in the cerebellum and right insula ( p TFCE < 0.05). Mean diffusivity was generally lower in the AUD group ( p TFCE < 0.05). AUD had lower coclassification of nodes between ventral attention and default mode networks and higher coclassification between nodes of visual, default mode, and somatomotor networks. Additionally, AUD had higher fiber density between an adjacent pair of nodes within the default mode network. Conclusions: Our results indicate that emerging adulthood AUD subjects may have differential patterns of FA and distinct differences in structural connectomes compared with CON. These data suggest that such alterations in microstructure and structural connectivity may uniquely characterize early stages of AUD and/or a predisposition for development of AUD. Abstract : Studies of white matter (WM) microstructure in early adulthood alcoholism have yielded inconsistent findings. To understand how early alcohol dependence affects WM, we compared indices of WM microstructure and WM tract connectivity between emergent alcohol use disorder and age‐matched social drinkers. The young alcohol dependent group had differential patterns of WM integrity and structural connectivity compared to the social drinking sample. Taken together, the results could indicate either a predisposition to and/or early consequence of heavy alcohol exposure.